TLR9 and STING agonists synergistically induce innate and adaptive type‐II IFN. Issue 4 (5th February 2015) - Temizoz, Burcu; Kuroda, Etsushi; Ohata, Keiichi; Jounai, Nao; Ozasa, Koji; Kobiyama, Kouji; Aoshi, Taiki; Ishii, Ken J.
<x xml:space="preserve">Abstract</x> Agonists for TLR9 and Stimulator of IFN Gene (STING) act as vaccine adjuvants that induce type‐1 immune responses. However, currently available CpG oligodeoxynucleotide (ODN) (K‐type) induces IFNs only weakly and STING ligands rather induce type‐2 immune responses, limiting their potential therapeutic applications. Here, we show a potent synergism between TLR9 and STING agonists. Together, they make an effective type‐1 adjuvant and an anticancer agent. The synergistic effect between CpG ODN (K3) and STING‐ligand cyclic GMP–AMP (cGAMP), culminating in NK cell IFN‐γ (type‐II IFN) production, is due to the concurrent effects of IL‐12 and type‐I IFNs, which are differentially regulated by IRF3/7, STING, and MyD88. The combination of CpG ODN with cGAMP is a potent type‐1 adjuvant, capable of inducing strong Th1‐type responses, as demonstrated by enhanced antigen‐specific IgG2c and IFN‐γ production, as well as cytotoxic CD8+ T‐cell responses. In our murine tumor models, intratumoral injection of CpG ODN and cGAMP together reduced tumor size significantly compared with the singular treatments, acting as an antigen‐free anticancer agent. Thus, the combination of CpG ODN and a STING ligand may offer therapeutic application as a potent type‐II IFN inducer.